Pakistan Army Green Book 2013 : National Security Issues - Pakistan Army; Edited by Ikram Ul Haq, Lt. Gen. ; Lodhi, Naeem Khalid, Lt. Gen. ; Hanif, Khawar, Lt. Gen. ; Firdous, Nayyer, Brigador Dr. ; Khan, Muhammad, Brigadier Dr. (GHQ, Rawalpindi Pakistan Army, 2013)
The Contents of this Book are Writers' Personal Views. The Statements, Facts and opinions by the authors in the green book do npt imply the offical policy of the institution, editors or the Publishers.
Include Color Illustration
Keywords: Pakistan. Army -- Pakistan. -- Army -- Periodicals